Self-Awareness and Speaking Skill of Vocational Students of Sinar Metta Batam - Dewi, Desi Surlitasari; Ervayuni, Anggia (English Department, University of Riau Kepulauan, Batam,Indonesia, 2021)
Speaking is the crucial part to master in English, it can help people to connected with other people around the world. But in fact, students face some difficulties to learning English. The difficulties caused of several things; teaching strategy, curriculum, environment or the learners themselves. There are several emotional matters that play the role and influence students ability in learning, one of them is self-awareness. The objective of the study was to find the correlation between self-awareness and students’ speaking skill. The population of the study was the tenth grade of students at Vocational High School Sinar Metta Batam. The sampling technique was using census or total sampling because the population less than 100. The data obtained from questionnaire for self-awareness and speaking test. This research was using quantitative method to find out the result, where result of calculating rcount < rtable (0.27